A retrospective observational study analyzing the clinical presentation, complications, and outcome of Melioidosis in a tertiary healthcare center in South India (Asian Journal of Medical Sciences, 2025)
Background: Melioidosis is caused by a saprophytic environmental Gram-negative bacterium Burkholderia pseudomallei. It is widespread in Northern Australia and South-east Asia and has shown an increasing trend in India. There are limited studies done in South India analyzing the clinical profile of melioidosis patients, hence the need for this study.Aims and Objectives: To analyze the demographic data, clinical presentation, investigations, treatment, complications, and outcomes in patients with melioidosis.Materials and Methods: A retrospective observational study was done on 35 patients who were admitted to a tertiary health care centre in South India from January 2017 to March 2025, who had culture-proven melioidosis. The spectrum of clinical profiles was analyzed.Results: 35 patients were studied, 68.6% were male, 71.5% were in the age group of 45–65 years, clustering of cases was seen around the rainy months, fever and cough were the most common symptoms (94.3% and 42.9%, respectively), diabetes mellitus was the most common risk factor. The most common presentation was abscess (45.71%) and pneumonia (37.1%). 42.9% required intensive care, and 2 out of 35 patients died.Conclusion: Melioidosis is an acute infection that may lead to sepsis and multi-organ dysfunction. It is often misdiagnosed due to variable clinical presentation and a lack of awareness among clinicians. Diabetes is the most common risk factor. Pneumonia, abscesses, and hepatosplenomegaly should raise suspicion of melioidosis. Blood cultures are positive in almost all cases and respond well to carbapenems/ceftazidime with cotrimoxazole. Early diagnosis and prompt treatment are paramount in improving patient outcomes.